Improved Detection of in vivo Human NK Cell-Mediated Antibody-Dependent Cellular Cytotoxicity Using a Novel NOG-FcγR-Deficient Human IL-15 Transgenic Mouse - Katano, Ikumi; Ito, Ryoji; Kawai, Kenji; Takahashi, Takeshi (Frontiers in Immunology, 2020)
We generated an NOD/Shi-scid-IL2Rγnull (NOG) mouse deficient for the Fcer1g and Fcgr2b genes (NOG-FcγR−/− mice), in which monocytes/macrophages do not express activating (FcγRI, III, and IV) or inhibitory (FcγRIIB) Fcγ receptors. Antibody-dependent cellular cytotoxicity (ADCC) by innate immune cells was strongly reduced in this strain. Thus, while the growth of xenogeneic human tumors engrafted in conventional NOG mice was suppressed by innate cells upon specific antibody treatment, such growth inhibition was abrogated in NOG-FcγR−/− mice. Using this novel strain, we further produced NOG-FcγR−/−-mice expressing human IL-15 (NOG-FcγR−/−-hIL-15 Tg). The mice inherited unique features from each strain, i.e., the long-term sustenance of human natural killer (NK) cells, and the elimination of mouse innate cell-mediated ADCC. As a result, segregation of human NK cell-mediated ADCC from mouse cell-mediated ADCC was possible in the NOG-FcγR−/−-hIL-15 Tg mice. Our results suggest that NOG-FcγR−/−-hIL-15 Tg mice are useful for validating the in vivo function of antibody drug candidates.